Effect Of Caffeine On Exercise Performance: Current Review - Yusuf Buzdağlı; Günay Eskici; Erdinç Şıktar; Aslıhan Tekin (Selcuk University, 2021)
Caffeine is an ergogenic supplement that has been attracting attention in the sports community for many years. It has been proven in many studies that coffee consumption has a positive effect on exercise performance. This study was conducted to (I) examine the effects of caffeine on exercise performance and different performance areas, (II) to provide comprehensive recommendations on the use of caffeine in sports and exercise, and (III) to identify existing gaps in the literature and to make key recommendations for future research. This current review article provides an analytical look at studies involving the use of caffeine for the physical, physiological, and cognitive performance of individuals, and discusses factors that may affect the ergogenic effects of caffeine on the different proposed activities. Within the scope of this review, previously published studies are published using broad keywords related to "caffeine" through "ELSEVIER Science Direct (SciVerse), Taylor amp; Francis, EBSCOhost-Academic Search Complete, PubMed and SpringerLink, Google Scholar" databases until January 2021. scan has been done. As a result, caffeine has been reported to increase endurance performance by 2-4% and improve short-term and intense intensity exercise performance in highly trained individuals. The improving effect of caffeine on cognitive performance supports its use as an ergogenic supplement. Caffeine has been shown to increase sympathetic nervous system activity and release fatty acids from adipose and / or intramuscular stores. This mechanism, which occurs indirectly through increased adrenaline levels, has the potential to increase the availability of fatty acids for oxidation and the resting metabolic rate. At the same time, it has been observed that caffeine does not cause dehydration and is a reliable ergogenic supplement in this respect. Ergogenic effect of caffeine in future studies; It should be clarified by focusing on questions such as what time of the day caffeine consumption affects caffeine ergogenicity, what is the effect of age on caffeine ergogenicity, caffeine intake according to athlete's training level, and the importance of genotype in terms of caffeine consumption.